2017
DOI: 10.1002/ijgo.12366
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of obstetric and anesthetic management of patients with placenta accreta spectrum disorders

Abstract: Placenta previa and accreta coexist in many patients, leading to substantial bleeding related to the degree of myometrial invasion. An interdisciplinary team approach plus the use of combined spinal-epidural anesthesia, transitioning to general anesthesia, were advisable and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…In our study, conversion to GA was performed in 21 (30%) cases, which is in accordance with the findings of a retrospective study by Lilker et al, where 29% of the patients with PAS underwent conversion to GA due to excessive bleeding [17]. Riveros-Peres et al suggested that, after the umbilical cord has been clamped, conversion of CSE to GA should be used as a routine anesthetic practice, especially when a protocol of massive hemorrhage is being employed [18]. The application of a neuraxialonly technique can avert certain complications of GA, provide better pain control, and minimize the need for transfusion [19].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, conversion to GA was performed in 21 (30%) cases, which is in accordance with the findings of a retrospective study by Lilker et al, where 29% of the patients with PAS underwent conversion to GA due to excessive bleeding [17]. Riveros-Peres et al suggested that, after the umbilical cord has been clamped, conversion of CSE to GA should be used as a routine anesthetic practice, especially when a protocol of massive hemorrhage is being employed [18]. The application of a neuraxialonly technique can avert certain complications of GA, provide better pain control, and minimize the need for transfusion [19].…”
Section: Discussionsupporting
confidence: 90%
“…[4][5][6][7] On the contrary, it is recommended that PAS patients be managed in tertiary care centers, underscoring the importance of resource availability and coordinated multispecialty care. 8 Surgical management of PAS entails multiple interventions aimed at limiting bleeding. The use of prophylactic hypogastric balloons is controversial, as it does not account for all the proximal uterine blood supply; and some authors have shown their inefficacy in cases of placenta percreta.…”
Section: Discussionmentioning
confidence: 99%
“…Some centers described a decreased use of GA over time, [7][8][9] while others reported increased use. [10][11][12] These data suggest that there is no clear consensus on the preferred choice of primary anesthetic. In cases in which NA is the preferred primary anesthetic, there was substantial variability in rates of sustained use of NA for the entire case (5-72%) and intraoperative conversion from NA to GA (7-70%).…”
Section: General Versus Neuraxial Anesthesiamentioning
confidence: 99%